2018
DOI: 10.1021/acssuschemeng.8b00769
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Soluble–Insoluble Upper Critical Solution Temperature-type Poly(methacrylamide-co-acrylic acid)–Cellulase Biocatalyst for Hydrolysis of Cellulose into Glucose

Abstract: How to improve the accessibility of immobilized cellulase to insoluble cellulose and recover immobilized enzyme from remaining insoluble substrate is a challenge to the efficient hydrolysis of cellulose into glucose. The objective of this work is to solve the problems mentioned above by the immobilization of cellulase onto poly(methacrylamide-coacrylic acid) (PMAAc), developing a reversibly soluble− insoluble biocatalyst with upper critical solution temperature (UCST) of 16 °C. The as-prepared PMAAc−cellulase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 43 publications
(72 reference statements)
2
31
0
Order By: Relevance
“…It has been observed that a greater amount of cellulase increases the intermolecular steric barrier and limits the reaction efficiency of the cellulase to the support 50 . Furthermore, in the literature, an excess of cellulase immobilization on the support surface will lead to steric blocking among enzymes, reducing their activity by blocking active sites 51‐53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that a greater amount of cellulase increases the intermolecular steric barrier and limits the reaction efficiency of the cellulase to the support 50 . Furthermore, in the literature, an excess of cellulase immobilization on the support surface will lead to steric blocking among enzymes, reducing their activity by blocking active sites 51‐53 …”
Section: Resultsmentioning
confidence: 99%
“…50 Furthermore, in the literature, an excess of cellulase immobilization on the support surface will lead to steric blocking among enzymes, reducing their activity by blocking active sites. [51][52][53] The effects of immobilization temperature and pH are also examined. As shown in Figure 8(c,d), the highest amount of cellulase loading was displayed to be pH 5 and temperature 50 C. At a higher pH, this may be caused by the destruction of the hydrogen bond, which determines the partial inactivation and support of the enzyme.…”
Section: Influences Of Immobilizing Conditionsmentioning
confidence: 99%
“…Lignocellulosic materials fulfill some properties required in a promising support, such as large availability and low cost [86]. Finally, relevant progress in new innovative supports should also be noted such as the cases of biomimetic films [87], nanomaterials [88] and stimuli-responsive smart materials [89].…”
Section: Recent Advances On Cellulases Immobilizationmentioning
confidence: 99%
“…To solve this problem, poly(methacrylamide-co-acrylic acid) (PMAAc) with UCST of 16°C was utilized to immobilized cellulase enzyme in order to enhance the stability at high temperature and to enable easy recovery of enzyme below UCST. The hydrolysis rate of insoluble cellulose to glucose at elevated temperature was significantly enhanced with the aid of newly developed biocatalyst while retaining the enzyme activity [77].…”
Section: Improvement In Catalytic Activitymentioning
confidence: 99%